2023
DOI: 10.1002/adfm.202302753
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Control of Radiations and In‐Band Co‐Polarized Reflections by a Single Programmable Metasurface

Abstract: Integrated control of radiated and reflected electromagnetic (EM) waves is of great importance in information science and engineering, which are mostly achieved by elaborately integrating metasurfaces and antennas. However, most of the radiation‐reflection‐integrated designs remain difficulties to modulate the radiated waves directly without cascading additional radio‐frequency (RF) modules. More importantly, the completely independent control of radiated waves and in‐band co‐polarized reflected waves has rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…The working mechanism of the proposed SFPRS meta-atom shares some similarities with the radiation-reflection-switching metasurface, [57] as both involve radiation/sensing and reflec-tion functions. The difference is that the radiation-reflectionswitching metasurface needs switching components to alternate between the two functions, while the proposed SFPRS meta-atom can perform the two functions simultaneously at the cost of low sensing loss (≈−10 dB).…”
Section: Discussionmentioning
confidence: 96%
“…The working mechanism of the proposed SFPRS meta-atom shares some similarities with the radiation-reflection-switching metasurface, [57] as both involve radiation/sensing and reflec-tion functions. The difference is that the radiation-reflectionswitching metasurface needs switching components to alternate between the two functions, while the proposed SFPRS meta-atom can perform the two functions simultaneously at the cost of low sensing loss (≈−10 dB).…”
Section: Discussionmentioning
confidence: 96%
“…Programmable metasurfaces have huge capability to control the spatial EM beams in real time, since the EM features of the unit cells can be manipulated by external DC voltages in a programmable way. Generally, the programmable metasurfaces can be broadly classified into two categories: reflection type , and transmission type. The reflection-type design is limited by the presence of blocking effects, and both types exhibit disadvantages of high profile.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the programmable metasurfaces can be broadly classified into two categories: reflection type , and transmission type. The reflection-type design is limited by the presence of blocking effects, and both types exhibit disadvantages of high profile. As a result, the architecture of integrated programmable metasurfaces , has emerged as a subject of considerable interests among researchers, as it offers a solution to overcome these drawbacks. However, simultaneous controls of the receiving and transmitting beams using a shared aperture have not been sufficiently addressed with an effective solution in designing the programmable metasurface.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Tian et al reported a programmable metasurface for the control of both radiated and reflected waves. 28 Although various new applications have been developed, programmable metasurfaces studied so far are mostly focusing on the manipulation of single linearly polarized (LP) electromagnetic wave. 29−33 As one of the fundamental properties of electromagnetic waves, polarization plays a key role in many physical phenomena and applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In ref , an integrated multifunctional programmable metasurface was presented for analog signal processing, polarization conversion, beam manipulation, and near-field sensing. Most recently, Tian et al reported a programmable metasurface for the control of both radiated and reflected waves …”
Section: Introductionmentioning
confidence: 99%